2021
DOI: 10.1002/jor.25161
|View full text |Cite
|
Sign up to set email alerts
|

Acute and severe trabecular bone loss in a rat model of critical illness myopathy

Abstract: Prolonged mechanical ventilation for critically ill patients with respiratory distress can result in severe muscle wasting with preferential loss of myosin. Systemic inflammation triggered by lung mechanical injury likely contributes to this myopathy, although the exact mechanisms are unknown. In this study, we hypothesized that muscle wasting following mechanical ventilation is accompanied by bone loss. The objective was to determine the rate, nature, and extent of bone loss in the femora of rats ventilated u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
(90 reference statements)
0
3
0
1
Order By: Relevance
“…TRPV4 has also been implicated in macrophage activation leading to lung injury following mechanical ventilation. These issues have also been reported in a rat model of immobilization and mechanical ventilation [20] in which it was shown that the pharmacologic immobilization of rats was accompanied by marked trabecular bone loss, thus liberating calcium into the circulation and possibly contributing to the inflammation described by Michalick and Kuebler [19].…”
Section: Extracellular Calcium and Inflammationmentioning
confidence: 57%
See 1 more Smart Citation
“…TRPV4 has also been implicated in macrophage activation leading to lung injury following mechanical ventilation. These issues have also been reported in a rat model of immobilization and mechanical ventilation [20] in which it was shown that the pharmacologic immobilization of rats was accompanied by marked trabecular bone loss, thus liberating calcium into the circulation and possibly contributing to the inflammation described by Michalick and Kuebler [19].…”
Section: Extracellular Calcium and Inflammationmentioning
confidence: 57%
“…This has been demonstrated in cardiomyocytes [45]. A similar mechanism has been described for the initiation of inflammation in mechanical ventilation [20], and a related mechanism has been implicated following cardiac ischemia, also involving a Ca 2+ /calmodulin regulated kinase [46]. It is unclear how much circulating Ca is necessary to trigger these latter effects, or if there is a threshold for circulating Ca to contribute to these effects.…”
Section: Other Clinical Conditionsmentioning
confidence: 76%
“…Se postula que esta asociación podría intensificarse a medida que aumentan los días de permanencia en la UCI debido a la severidad de la enfermedad y la activación de cascadas inflamatorias, lo que podría predisponer a una mayor probabilidad de lesión de las fibras musculares o denervación de las mismas 20 . De este modo, Gugala et al 21 destacan que los mecanismos patofisiológicos de la miopatía evolucionan con el tiempo durante la estancia en UCI, involucrando disfunción en la excitabilidad de las membranas musculares, desbalance en la homeostasis del calcio, fallo bioenergético y problemas en la funcionalidad de las proteínas motoras.…”
Section: Discussionunclassified
“…We do not have evidence implicating bone-released TGF-β's involvement in immobilization to date. However, a recent study by Gugala et al [31] provides suggestive information. Studies of a rat model of critical illness myopathy developed by Llano Diez et al [32] have shown that by pharmacologically immobilizing rats and mechanically ventilating them for 10 days, a model that reproduces the effects of immobilization and the mechanical ventilation of patients in intensive care for COVID-19 respiratory disease, the loss of appendicular skeletal muscle mass and, in particular, myosin, occurs in tight correlation with the loss of trabecular bone, as determined by serial micro computed tomography of the femurs of rats studied from 0-10 days post-immobilization.…”
Section: Evidence Suggesting That Immobilization Plays a Role In Tgf-...mentioning
confidence: 95%